Intermolecular cross-correlations in the dielectric response of glycerol. Issue 20 (14th May 2020) - Gabriel, Jan Philipp; Zourchang, Parvaneh; Pabst, Florian; Helbling, Andreas; Weigl, Peter; Böhmer, Till; Blochowicz, Thomas
Abstract : We suggest a way to disentangle self- from cross-correlations in the dynamic susceptibility of the glass former glycerol by combining dielectric relaxation (BDS) with light scattering (DDLS), field cycling NMR, and shear compliance (SC) data. Abstract : We suggest a way to disentangle self- from cross-correlation contributions in the dielectric spectra of glycerol. Recently it was demonstrated for monohydroxy alcohols that a detailed comparison of the dynamic susceptibilities of photon correlation and broadband dielectric spectroscopy allows to unambiguously disentangle a collective relaxation mode known as the Debye process, which arises due to supramolecular structures, and the α-relaxation, which proves to be identical in both methods. In the present paper, we apply the same idea and analysis to the paradigmatic glass former glycerol. For that purpose we present new light scattering data from photon correlation spectroscopy measurements and combine these with literature data to obtain a data set covering a dynamic range from 10 −4 –10 13 Hz. Then we apply the above mentioned analysis by comparing this data set with a corresponding set of broadband dielectric data. Our finding is that even in a polyalcohol self- and cross-correlation contributions can approximately be disentangled in that way and that the emerging picture is very similar to that in monohydroxy alcohols. This is further supported by comparing the data with fast field cycling NMR measurements and dynamic shear relaxation data from the literature, and it turns out that, within the described approach, the α-process appears very similar in all methods, while the pronounced differences observed in the spectral density are due to a different expression of the slow collective relaxational contribution. In the dielectric spectra the strength of this peak is reasonably well estimated by the Kirkwood correlation factor, which supports the view that it arises due to dynamic cross-correlations, which were previously often assumed to be negligible in dielectric measurements.